Discrimination index, difficulty index, and distractor efficiency in MCQs English for academic purposes midterm test - Sri Rejeki; Angela Bayu Pertama Sari; Sutanto Sutanto; Dwi Iswahyuni; Devita Widyaningtyas Yogyanti; Helta Anggia (Universitas Sarjanawiyata Tamansiswa, 2023)
Test item analysis in language learning plays a crucial role in ensuring that the test can be an effective assessment tool in the learning process. It is a quantitative study that aimed to analyze Multiple Choice Questions of reading sections in English for Academic Purposes (EAP) subject for non-English majors to find out the Discrimination Index (DI), Difficulty Index (DIF), and Distractor Efficiency (DE). The participants of this study were first-year students majoring in the civil engineering program at Universitas Muhammadiyah Surakarta. Researchers collected the primary data from the answer sheets of the reading section. The data analysis was conducted by using Microsoft Excel and uploaded to Anates. It quickly gave the result of all the calculations of DI, DIF, and DE. The findings revealed the DI and DIF of this test were not good because most of the results were poor DI and too easy DIF, which meant that most test items needed modifications and distractors. Most distractors used in this test were not functional and must be removed, changed, or modified.